Ratios of UV, PAR and NIR components to global solar radiation measured at Botucatu site in Brazil - Escobedo, João Francisco [UNESP]; Gomes, Eduardo N. [UNESP]; Oliveira, Amauri R.; Soares, Jacyra (Pergamon-Elsevier B.V. Ltd, 2011)
The relationships between the four radiant fluxes are analyzed based on a 4 year data archive of hourly and daily global ultraviolet (I(UV)), photosynthetically active-PAR (I(PAR)), near infrared (I(NIR)) and broadband global solar radiation (I(G)) collected at Botucatu, Brazil. These data are used to establish both the fractions of spectral components to global solar radiation and the proposed linear regression models. Verification results indicated that the proposed regression models predict accurately the spectral radiant fluxes at least for the Brazilian environment. Finally, results obtained in this analysis agreed well with most published results in the literature. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Ultraviolet radiation; Photosynthetically active radiation; Near infrared solar radiation; Global solar radiation; Brazil